If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -6) = 9(x + -2) Reorder the terms: 3(-6 + x) = 9(x + -2) (-6 * 3 + x * 3) = 9(x + -2) (-18 + 3x) = 9(x + -2) Reorder the terms: -18 + 3x = 9(-2 + x) -18 + 3x = (-2 * 9 + x * 9) -18 + 3x = (-18 + 9x) Add '18' to each side of the equation. -18 + 18 + 3x = -18 + 18 + 9x Combine like terms: -18 + 18 = 0 0 + 3x = -18 + 18 + 9x 3x = -18 + 18 + 9x Combine like terms: -18 + 18 = 0 3x = 0 + 9x 3x = 9x Solving 3x = 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 3x + -9x = 9x + -9x Combine like terms: 3x + -9x = -6x -6x = 9x + -9x Combine like terms: 9x + -9x = 0 -6x = 0 Divide each side by '-6'. x = 0 Simplifying x = 0
| 6-4(1-2x)=-23+3x | | 23+x=33 | | -2y^2+3y=-14 | | 6.4x=0.64 | | p+.03p=154.5 | | x-3.4=3.6 | | 63=-15+x | | 6.4x=.064 | | 6-x=4-.5x | | 2x^3+16y^3=0 | | 2x-11=83 | | 63=-15+4 | | x/2-9=-5 | | 8m-5=3 | | Y-9=42 | | -9-6x+7x=7x+3x | | -8.7-5z-1.6-z=-5z+7.6 | | -3(3y+2)-10=-6(y+4)+3y | | 2b+4b+20=3(2b+10) | | 17+y=37 | | 7y+3=-4 | | 5(n-7)-(6-4n)=8n | | 2t+5=9-t | | s+(3s+0.22)+(s-0.22)=4.6 | | (4+256)+(445*86)= | | x-0.08=0.1 | | -5x-8(x+5)=-4(3x+8) | | 3(2+b)-4b=b+16 | | -8(m+8)=-9+3m | | (4+256)+(47*86)= | | 17+y=20 | | x+2=93 |